2020
DOI: 10.1016/j.celrep.2020.107831
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Non-canonical Cysteines in Human VH Repertoire Revealed by Immunogenetic Analysis

Abstract: Highlights d NGS-based non-canonical cysteine landscape in human V H s d 1 to 8 non-canonical cysteines and up to 30% in long CDR-H3s d An array of potential disulfide motifs adds paratope diversity d Non-canonical cysteines in human V H s are reminiscent of lower animals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Previously, we discovered CDR-H3 length-dependent usage of human IGHD germline genes [ 28 ]. Such CDR-H3 length-dependent usage of non-canonical cysteines was extensively characterized in human VH repertoires [ 30 ] and in other animals such as chicken [ 31 ], bovine [ 32 ], shark and camelid [ 33 ]. Intrigued by the roles of human IGHD gene segments in shaping human antibody CDR-H3 diversity, we analyzed the human IGHD germline gene usage of natural antibodies derived from 8 healthy donors and 44 DENV acutely infected patients—the same dataset we used in section Antibody heavy chain CDR3-dependent usage of human IGHJ4 and IGHJ6.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we discovered CDR-H3 length-dependent usage of human IGHD germline genes [ 28 ]. Such CDR-H3 length-dependent usage of non-canonical cysteines was extensively characterized in human VH repertoires [ 30 ] and in other animals such as chicken [ 31 ], bovine [ 32 ], shark and camelid [ 33 ]. Intrigued by the roles of human IGHD gene segments in shaping human antibody CDR-H3 diversity, we analyzed the human IGHD germline gene usage of natural antibodies derived from 8 healthy donors and 44 DENV acutely infected patients—the same dataset we used in section Antibody heavy chain CDR3-dependent usage of human IGHJ4 and IGHJ6.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a possible implication for data mining in the NGS repositories for discovering therapeutic antibody candidates in future. Also, large-scale NGS analysis of individual antibodyome will lead to improved insights into overall diversity of the human antibody repertoire and B cell immunogenetics ( 15 17 ).…”
mentioning
confidence: 99%
“…Interestingly, we found that 20% of receptors in these rare shared, expanding lineages contain multiple cysteines in their HCDR3s, in contrast to only 10% of the receptors in the whole repertoire. Such sequence patterns with cysteine pairs in the HCDR3 have been associated with stabilization of the HCDR3 loop by forming disulfide bonds with particular patterns and spacings of the cysteines (Lee et al, 2014; Prabakaran and Chowdhury, 2020). Disulfide bonds in the HCDR3 can decrease the conformational flexibility of the loop, thus decreasing the entropic cost of binding to improve the affinity of the receptor (Almagro et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, three distinct SARS-CoV-2-specific mAbs were found to be close in sequence to HCDR3s in our data, with only one amino acid difference, and one of these mAbs also had a matching V gene (Table 1). Among these, we found a class of antibodies containing multiple cysteines in their HCDR3s, with the potential to form disulfide bonds to enhance their affinity to antigens and paratope diversity (Almagro et al, 2012; Lee et al, 2014; Prabakaran and Chowdhury, 2020).…”
Section: Resultsmentioning
confidence: 99%